Investigation of a reverse-cross flow combustor with varying fuel injection momentum. (May 2019) - Gupta, Shreshtha Kumar; Arghode, Vaibhav Kumar
Highlights: The effect of fuel injection momentum on flow field is investigated for a reverse-cross flow combustor. Higher fuel jet momentum deflects the air jet significantly. OH * chemiluminescence images suggest that the reaction zone is near the air jet. Abstract: The primary objective of this work is to aid the design of a gaseous fuelled reverse-cross flow combustor based on critical factors such as flow field, temperature field, residence time distribution and recirculation ratio of the product gases inside the combustor. In the present work, the effect of fuel injection momentum on these critical factors is investigated by using different fuel injection diameters at same equivalence ratio. The effect of variation of equivalence ratio for the highest fuel injection momentum case (smallest fuel injection diameter) is also studied. A lab scale combustor with full optical access having reverse-cross flow geometry is employed for experimental analysis. Three-dimensional computations were performed on a geometrical model of this combustor under reacting flow conditions using a commercial software ANSYS-Fluent. Methane is used as the fuel. The numerically calculated flow field inside the combustor is observed to be very sensitive to the fuel injection momentum. As the fuel injection momentum increases, the air jet gets deflected and this significantly affects the flow field inside the combustor such that the recirculation ratio profile changes and the residence time distribution becomes unfavourable. Experimentally obtained OH * chemiluminescence images suggest that the reaction zone moves upward with increase in fuel injection momentum and its intensity increases with increase in equivalence ratio. The measured CO and NOx emissions at exhaust suggest that CO increases and NOx decreases with increase in fuel injection momentum. It is found that the effect of fuel injection momentum is pronounced when the fuel injection momentum is higher than a critical value, above which, the flow field, thermal field, and the reaction zone location are affected significantly.